Long-Term Recidivism Studies Show That Desistance Is the Norm - Hanson, Robert Karl (Criminal justice and behavior, 2018)
A criminal history record is a valid indicator of the propensity for rule violation, and such records are rightly used in applied decision making both within and outside of the criminal justice system (e.g., employment screening). A criminal conviction, however, is a time dependent risk factor. During the past decade, researchers have examined desistance using statistical models of residual hazards. These studies find that after about 10 years offense-free (5 years for juveniles), the risk presented by most individuals with a criminal record is not meaningfully different from that of the general population. Similar time-free effects are found for both sexual and nonsexual offenses. Given that desistance is almost inevitable, record retention and access policies need to carefully consider the consequences of decisions being based on old records with little information value.